2020
DOI: 10.3390/educsci10110304
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate Flexibility and Self-Discipline: Student Adaptation to Emergency Remote Teaching in an Integrated Engineering Energy Course during COVID-19

Abstract: The global pandemic of COVID-19 brought about the transition to Emergency Remote Teaching (ERT) at higher education institutions across the United States, prompting both students and the faculty to rapidly adjust to a different modality of teaching and learning. Other crises have induced disruptions to academic continuity (e.g., earthquakes, hurricanes), but not to the same extent as COVID-19, which has affected universities on a global scale. In this paper, we describe a qualitative case study where we interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
232
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(247 citation statements)
references
References 42 publications
8
232
0
7
Order By: Relevance
“…This is not surprising given the greater childcare obligations with school closures and that women spend more time doing unpaid care work compared to men [32]. In an interview study of engineering students, women reported having to spend more time on domestic duties while men described having more free time after the transition to remote learning during the Spring 2020 semester [71]. Together this suggests that the COVID-19 pandemic has exacerbated gender inequities and could have long-term negative impacts on women’s education and careers that are not captured in simply examining student course grades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising given the greater childcare obligations with school closures and that women spend more time doing unpaid care work compared to men [32]. In an interview study of engineering students, women reported having to spend more time on domestic duties while men described having more free time after the transition to remote learning during the Spring 2020 semester [71]. Together this suggests that the COVID-19 pandemic has exacerbated gender inequities and could have long-term negative impacts on women’s education and careers that are not captured in simply examining student course grades.…”
Section: Discussionmentioning
confidence: 99%
“…Setting up robust systems of communication among students, instructors, student support staff members, and administrators might improve the academic climate for all stakeholders and prepare us better for future emergencies or needs to change instruction rapidly. Indeed, an interview study with engineering students found that faculty members communicating care and increasing flexibility was a key element for supporting students [71]. In another study, students indicated the need for constant communication from instructors during remote learning [78].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the situations we have experienced and continue to experience, due to COVID-19, all citizens have had to adapt to distance learning. Students must embrace new ways of learning, so individually we must show compassion, respond empathically, and voluntarily help other colleagues who are in difficult situations [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies [e.g., 6,7] used the activity-centered analysis and design (ACAD) framework to design ERT in New Zealand, and Karakaya [7] focused on a human-centered approach. In the same vein, several researchers have focused on various pedagogical constraints in remote teaching activities [8][9][10][11][12], however, none have specifically developed the principles of implementing ERT, thus, this study aims to fill this gap.…”
Section: Introductionmentioning
confidence: 99%